Attachment Style Predicts Emotion Regulation, Help‐Seeking, and Recovery in Psychosis - Jacqui Tiller; Tess Maguire; Katherine Newman‐Taylor (Mental Health Science, 2025)
ABSTRACT Untreated psychosis can have a devastating impact on individuals and their families. Recommended therapies are underutilised. Attachment theory provides a framework to understand intra‐ and interpersonal responses to threat cues, such as voices and paranoia, which affect recovery. This is the first study to test a coherent set of theory‐driven predictions about the impact of attachment style on people's ability to manage distress associated with psychosis, and seek help effectively. We used a cross‐sectional design to examine the impact of attachment style on emotional regulation, help‐seeking intentions, service engagement, and clinical and recovery outcomes in people with psychosis. We recruited a total of 65 participants with psychosis from community and NHS pathways. Participants completed standardized measures of predictor and dependent variables at one‐time point. Regression analyses showed that insecure attachment (anxious and avoidant) predicted more use of unhelpful emotional regulation strategies, less help‐seeking, and poorer clinical and recovery outcomes, with medium to large effects (p < 0.05). We found no effects for service engagement. Attachment style predicts intra‐ and interpersonal responses to threat in psychosis, and may partially account for the considerable variation in engagement with recommended therapies, and longer‐term outcomes. Routine assessment of attachment at initial service contact would identify people likely to struggle to seek and accept therapeutic interventions, who may in turn benefit from attachment‐congruent engagement efforts.